IMPROVING STUDENT LEARNING OUTCOMES ON CULTURAL DIVERSITY IN INDONESIA THROUGH DIORAMA MEDIA - Hutomo, Ignatius Bambang Purwo; Astutiningtyas, Erika Laras; Paramita, Astri (Jurnal PTK dan Pendidikan, 2025)
This class action research aims to improve the learning outcomes of fifth grade students of SDN Joho 1 Sukoharjo on the material of cultural diversity in Indonesia through the use of diorama media. The background of this research is the low learning achievement of students due to the lack of use of concrete media in the learning process. The research took place in two cycles, each cycle consisted of steps of planning, implementation, observation, and reflection. This study involved nine fifth grade students, consisting of seven male students and two female students. Data were collected through observation of learning activities and learning outcome tests at the end of each cycle. Data were analyzed descriptively quantitatively to assess the improvement of students' learning achievement. The research findings showed an increase in students' learning achievement from cycle I to cycle II. Diorama media supports learners in understanding the material more effectively because it is able to present cultural concepts in a clear and interesting way. The conclusion of this study is that diorama media is effectively used to improve learners' learning achievement on the topic of cultural diversity in Indonesia.